Self-control, homicide offending, and homicide victimization - Meldrum, Ryan Charles (Routledge handbook of homicide studies, 2024)
This chapter reviews theory and research on the association between self-control, homicide offending, and homicide victimization. While much attention has been devoted to investigating the link between deficits in self-control and a wide variety of delinquent, criminal, and violent behaviors, far less attention has been devoted to empirical investigations focused on homicide offending and victimization as outcomes, despite strong theoretical rationales. Given this, the chapter also highlights research linking proxies for low self-control to homicide offending and victimization. It concludes by providing recommendations for future researchers to advance this neglected but important area of scholarship related to the nexus between self-control and homicide.